2016
DOI: 10.1186/s40529-016-0142-x
|View full text |Cite
|
Sign up to set email alerts
|

Salt tolerance of a wild ecotype of vetiver grass (Vetiveria zizanioides L.) in southern China

Abstract: BackgroundVetiver grass (Vetiveria zizanioides L.) is widely used in more than 120 countries for land management (e.g. rehabilitation of saline lands). A wild ecotype of vetiver grass was found in southern China in the 1950s, but little is known about its adaptability to saline stress. For the purpose of understanding its tolerance to salinity as well as corresponding tolerance mechanisms, in a greenhouse with natural lighting, seedlings were grown in culture solutions and subjected to a range of NaCl concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Similar results were observed by Jampasri et al (2017) who established that V. nemoralis could tolerate up to 333 mg/kg of soil Cd concentration under salt stress (EC 3.5 dS/m). However, Liu et al (2016) and Truong (1994) also showed that V. zizanioides had a salinity threshold of 10.0 and 8.0 dS/m, respectively, without Cd contamination. Generally, drought causes the increase in salt content in the farmland, and also the effect of drought or soil water stress decreased plant's ability to deal with heavy metals soil contamination.…”
Section: Shoot Height (Cm)mentioning
confidence: 94%
“…Similar results were observed by Jampasri et al (2017) who established that V. nemoralis could tolerate up to 333 mg/kg of soil Cd concentration under salt stress (EC 3.5 dS/m). However, Liu et al (2016) and Truong (1994) also showed that V. zizanioides had a salinity threshold of 10.0 and 8.0 dS/m, respectively, without Cd contamination. Generally, drought causes the increase in salt content in the farmland, and also the effect of drought or soil water stress decreased plant's ability to deal with heavy metals soil contamination.…”
Section: Shoot Height (Cm)mentioning
confidence: 94%
“…It is generally accepted that maintaining K + homeostasis in plant cells depends on the selective uptake of K + and the cellular compartmentalization and distribution of Na + and K + in various organs (Carden et al 2003). Thus, K + and Na + SA and ST in plants strongly correlate with salt tolerance (Liu et al 2016). The results showed that under salt stress, the Na + content significantly increased in various organs, and the uptake of K + decreased, thus increasing the Na + /K + in each organ.…”
Section: Cultivarsmentioning
confidence: 99%
“…Highvalue aromatic plants can be successfully grown on the marginal lands owing their potential to grow on impoverish soils, lower nutrient requirements, better water use efficiency and diminish air pollution (Litskas, Chrysargyris, Stavrinides, & Tzortzakis, 2019). Marginal lands constrict agricultural productivity and profitability but could be utilized for the production of aromatic plants, which would not only ameliorate it but also provide higher benefit‐cost‐ratio and sequester C (Basak, Saha, Chinchmalatpure, & Manivel, 2018; Liu, Liu, Yao, & Ma, 2016).…”
Section: Why Aromatic Plants For the Cultivation Of Marginal Lands?mentioning
confidence: 99%